Pengaruh Pertumbuhan Ekonomi, Inflasi dan Investasi Terhadap Pengangguran di Provinsi Bali Tahun 1995-2014 - Bayu Dirga, I Nyoman; Aswitari, Luh Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 1, Januari 2017 (pp. 1 - 114), 2017)
Unemployment is the labor issue often faced by every country in the world, including developing countries. The unemployment rate is an important indicator for the economic development of a country in general. This study aimed to determine the effect simultaneously and partially economic growth (X1), inflation (X2) and investments (X3) of the Unemployment in province of Bali (Y). The data used in this research is secondary data. The data collected is done by non-participant observation. Data analysis techniques used in this research is multiple linear regression analysis. The test results with Eviews 6 obtain the results of economic growth (X1), inflation (X2), and investments (X3) simultaneously have significant effect on unemployment in the province of Bali (Y). In partial results of economic growth (X1), and inflation (X2) not have significant impact on unemployment in the province of Bali (Y), while variable investment (X3) have significant negative effect on unemployment in the province of Bali (Y).
Keywords: unemployment; economic growth; inflation; investment